2019
DOI: 10.1002/lt.25658
|View full text |Cite
|
Sign up to set email alerts
|

Changing Etiologies and Prognostic Factors in Pediatric Acute Liver Failure

Abstract: After the implementation of universal hepatitis A virus vaccination inArgentina, the outcome of pediatric acute liver failure (PALF) remains unknown. We aimed to identify variables associated with the risk of liver transplantation (LT) or death and to determine the causes and short-term outcomes of PALF in Argentina. We retrospectively included 135 patients with PALF listed for LT between 2007 and 2016. Patients with autoimmune hepatitis (AIH), Wilson's disease (WD), or inborn errors of metabolism (IEM) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…In the current issue, Mendizabal et al replicate the study performed in Bergamo, applying the same classification to a larger pediatric population in Argentina. They confirmed that the 2 groups have different features at presentation and outcome.…”
Section: Results Of 2 Studies On Children With Cld Presenting As Alfmentioning
confidence: 84%
See 4 more Smart Citations
“…In the current issue, Mendizabal et al replicate the study performed in Bergamo, applying the same classification to a larger pediatric population in Argentina. They confirmed that the 2 groups have different features at presentation and outcome.…”
Section: Results Of 2 Studies On Children With Cld Presenting As Alfmentioning
confidence: 84%
“…These results suggest that a rather large proportion of children presenting with ALF have clinical and biochemical features in keeping with an underlying chronic condition, can be easily distinguished from genuinely acute cases, and have a more favorable outcome if promptly recognized (Table ) . Importantly, many of these patients have an autoimmune etiology and, therefore, can benefit from a rescue immunosuppressive course …”
Section: Results Of 2 Studies On Children With Cld Presenting As Alfmentioning
confidence: 95%
See 3 more Smart Citations